Analysis of the Implementation of Drug Inventory Control with the Always Better Control-Economic Order Quantity-Reorder Point-Safety Stock Method - Nasution, Sri Lestari Ramadhani; Asthariq, Miftah; Girsang, Ermi (Open Access Macedonian Journal of Medical Sciences, 2022)
The pharmaceutical installation currently uses the consumption method in controlling drug supply, The purpose of this study is to provide a choice of other methods for controlling drug inventory. This study is a mix-method study with retrospective data for quantitative data and primary data for qualitative data. The research population used was all drug items during August 2020, totaling 269 items. The results showed the ABC method group A were 59 items, B were 64 items and C ware 146 items, the results of the EOQ method group A were 414 - 159, B were 414 - 159 and C were 778 - 1407 for certain types of drugs, the results of the method The ROP of group A were 12,027 – 962, group B were 6014 – 20,045 and group C were 3007 – 200 for certain types of drugs. The results of the SS method group A were 627 – 50, B were 314 -1054 and C were 157 – 11 for certain drug groups. Suggestions Hospital to try methods of controlling drug supplies other than the consumption method. And can provide training to human resources at the pharmacy.